2020
DOI: 10.1038/s41598-020-73378-5
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of intrahepatic cholestasis of pregnancy in a Chinese population

Abstract: Studies on the risk factors for intrahepatic cholestasis of pregnancy (ICP) in a population-based cohort are lacking. We assess the prevalence and risk factors of ICP in a Chinese population. In this study, a cohort study was conducted that included 12,200 eligible pregnant women. The overall incidence of ICP in this cohort was 6.06%. With increasing maternal age, the incidence of ICP decreased in women younger than 30 years of age but increased in those older than 30. With increasing pre-pregnancy BMI, the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
24
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 43 publications
(53 reference statements)
4
24
3
Order By: Relevance
“…The prevalence of ICP in this study was 3.15%, which was lower than that of other domestic studies [ 25 ]. A possible reason for this may be due to our comprehensive evidence-based management of patients with ICP and their good compliance.…”
Section: Discussioncontrasting
confidence: 82%
“…The prevalence of ICP in this study was 3.15%, which was lower than that of other domestic studies [ 25 ]. A possible reason for this may be due to our comprehensive evidence-based management of patients with ICP and their good compliance.…”
Section: Discussioncontrasting
confidence: 82%
“…Some causes of intrahepatic cholestasis include progressive familial intrahepatic cholestasis, primary biliary cholangitis, hepatitis, metastatic disease, certain medications, and intrahepatic cholestasis of pregnancy (ICP) [ 1 ]. ICP is the most common gestational disorder of the liver, with an occurrence that varies by ethnicity and geographic region (0.1-15.6%) [ 2 ]. Others include acute fatty liver disease of pregnancy, hemolysis with elevated liver enzymes and low platelets, and liver dysfunction from preeclampsia [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Results showed that the incidence of ICP increased with advancing maternal age if women were 30 years of age or older. The incidence of ICP decreased with increasing maternal age in women younger than 30 ( 28 ). In this study, the rate of ICP did not differ between the two groups.…”
Section: Discussionmentioning
confidence: 99%